Uncomputable: Play and Politics in the Long Digital Age by Alexander R. Galloway (review). - Gaboury, Jacob (Technology & Culture, 2023)
But the method is likewise deployed in Galloway's heavily archival treatment of the artificial evolution experiments of the mathematician Nils Aall Barricelli in the 1950s, which are recreated in section 4 using the visual programming language Processing, and which produced the cover image for the book itself. First, a warning: this book is not "about" uncomputability per se - though Galloway engages briefly with a range of recent work on the theoretical origins of computation and its inverse, uncomputability. Instead, uncomputability is a frame for thinking through the presumed inevitability of computation by foregrounding those various moments in the history of what would become our computational culture, in which computing fails to emerge, networks fray, and the digital atrophies.